Comparison of workload and academic performances of transfer and native students in an Asian educational context. Issue 2 (23rd February 2022) - Cheung, Kin; Chan, Eric S. W.; Ng, Jeremy; Tsang, Hilda; Leong, Hong-va
ABSTRACT: Post-secondary admission and community college (CC) transfer are two common routes of entry to baccalaureate study. Previous studies comparing the academic performances of native and transfer students have generated inconsistent findings and, furthermore, they were largely conducted in Western educational contexts. This study compared the workloads, grade point averages (GPA) and attrition rates of native and transfer students in an Asian educational context. Various measures related to GPA, credit load and attrition rate were collected from the institutional dataset of a Hong Kong university in 2019; this dataset contained records of 14, 141 native students and 7308 transfer students enrolled between 2012 and 2018. Results show that the transfer students experienced transfer shock and had heavier study loads but lighter non-academic loads than the native students. Despite the transfer shock, they attained a higher award GPA and had a lower attrition rate than their native counterparts. Discussion and implications are presented, in relation to transfer shock and transfer student success. In particular, this article argues that CC education does not necessarily produce academically inferior degree-seeking students and that CC transfer is a viable pathway to baccalaureate study.